Analisis Earning Per Share dalam Meningkatkan Pengembalian Saham - Bobby Billian Ramadhan; Erry Sunarya; Dicky Jhoansyah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Earning per share is profit per share which is a reference for investors in investing, the problems faced by PT. Indomobil Multi Jasa Tbk and PT. Buana Finance decreased its net income for two consecutive years. The purpose of the research is to find out the calculation of Earning Per Share (EPS) and the amount of stock returns on the company. This research method uses quantitative analysis descriptive analysis techniques that are used to describe in measuring stock returns. The data analysis technique uses Earning per Share calculations with a reference to the industry standard standard criteria. The results of the study show that theoretically the three companies value of EPS is not good because the calculation results are below the industry average standard. The results of the Earning per Share calculation can provide a reference for investors before deciding to invest to do an analysis of the company. Keywords: Earning per Share, Stock Returns, Net Profit